An evaluation of Lego-based Therapy and its impact on anxiety experienced by primary school-aged children with social communication difficulties - Lynch, Emma (2019)
Educational provision for children with social communication difficulties is constantly evolving to support not just social development, but also emotional development. With an emphasis on integrative and inclusive practices for all children, a range of interventions to support the diverse needs of this heterogeneous population are needed. Lego-based Therapy has captured interest over the past decade as an intervention that can support and nurture the social and emotional needs of children with social communication difficulties. This research evaluated the claim that Lego-based Therapy could reduce the anxiety experienced by primary school-aged children with social communication difficulties; a claim that has previously been unsupported. Using a pragmatic mixed-method approach, three case-studies were conducted. Quantitative data, from pre-and-post measures and single-case experimental designs (SCEDs), was triangulated with qualitative data, from semi-structured interviews. Numerical measures were collected from children, their parents and teachers in order to provide a holistic overview of a child’s anxiety. Pre- and post-analysis along with visual analysis from the embedded SCEDs provided tentative evidence to support the principal research question. According to self-report data from all three children, Lego-based therapy can be considered to have some positive effects on their reported anxiety following a 10-week Lego-based Therapy intervention. A similar finding was also reported by two of the three children’s teachers. However, contradictory findings came from parental ratings of their child’s anxiety, where a positive impact could not be determined. The qualitative analysis revealed core categories the facilitators and children perceived to be important in the success of Lego-based Therapy. Using the preliminary findings of the study, this research concludes that for primary school-aged children with social communication difficulties, Lego-based Therapy can have some positive effects on anxiety.